Implementing value engineering to generate recommended alternative to increase fish farmers’ exchange rate in West-Borneo - Sandero, Jovian; Santoso, Sugeng; Lawandra, Rio (Eximia, 2021)
Since 2014 to 2018, statistic has shown that the fish farmers’ exchange rate in West Borneo has an average of 99,47. This number is the evidence of low profitability rate experienced by the local fish farmers as the impact of ineffective existing business. By using the method of value engineering, this research aims to: 1) Introduce steps of implementing value engineering in West Borneo’s fish farming sector, 2) select best alternative to increase product value and 3) measure the potential impact of implementing the selected alternative. This research succeeded in implementing value engineering steps by adjusting its variable measurement indicator and also transforming value engineering into a more qualitative approach. Based on the method, Production of Fish Protein Hydrolisate is the selected alternative to increase product value. Finally, the potential impact is measured based on primary and secondary information resulting in an predicted fish farmers’ exchange rate of 207. This means that the value engineering method implemented has produced an alternative that can potentially contribute in increasing more than double of the existing fish farmers exchange rate and thus positively impacting their welfare. Finaly the government must support this alternative by regulating policies to accommodate the growth of this industry, such as the development of supporting infrastructure, promoting the use of fish hydrolisate as solution to national nutritional program and even policy to ease export overseas.